Indigenous Collaborative Governance: An Understanding of Decision-Making Process at Desa Adat in Bali, Indonesia - Wiyantari Sutaryantha, Md Putri; Kusumasari, Bevaola (Udayana Journal of Law and Culture, 2020)
The decision-making process that took place at desa adat (indigenous village) involved many actors and stakeholders from various elements of the community, to achieve a common goal. This research highlights the linkages of indigenous collaborative governance among actors involved in the decision-making process at Balinese Desa Adat, Indonesia. This research has, thus, discovered how indigenous collaborative governance was linked to the decision-making process and linked to the implementation of local governance, especially in the implementation of Adat in Bali Province. This study emphasizes the extensive use of public administration literature about collaborative governance and the decision-making process. Additionally, in-depth interviews and live experience in desa adat were conducted, as it is aimed to explore and understand more about the case. The result provided aligned with the conceptual framework because all of the actual implementation of the decision-making process at Desa Adat Peliatan met the criteria or indicators of collaborative governance. It showed that there was an involvement of indigenous collaborative governance in the process of decision-making at the desa adat level. The practical implication, in this case, is that collaboration matters in the decision-making process involving various elements of society with diverse interests.